2019
DOI: 10.56059/jl4d.v6i1.330
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in the Implementation of School-Based Teacher Professional Development: A Case from Kenya

Abstract: This study investigated how a school-based professional development programme, designed by the Headteacher and staff of a Kenyan primary school, and delivered by a Teacher Education in Sub-Saharan Africa (TESSA) team, supported teacher learning and growth. The TESSA team observed teaching in the classroom before the implementation of the school-based teacher professional programme. This was followed by the training of the teachers in the school. The TESSA team did an evaluation of the school-based training pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Regarding the concentration on individual characteristics, the bigger proportion of participants thought that they were not given attention to develop their acquired skills (n = 48; similar to 60.8%). Astonishingly, the results from the training environment in Table 1 reveal that the respondents got moderate degrees, conversely the findings in this aspect from Table 3 indicated negative outcomes, which is consistent with other studies [25][26][27]. Generally, the individual characteristics have to improve to meet the demands of the participants to improve the effectiveness of the TPs.…”
Section: Resultssupporting
confidence: 86%
“…Regarding the concentration on individual characteristics, the bigger proportion of participants thought that they were not given attention to develop their acquired skills (n = 48; similar to 60.8%). Astonishingly, the results from the training environment in Table 1 reveal that the respondents got moderate degrees, conversely the findings in this aspect from Table 3 indicated negative outcomes, which is consistent with other studies [25][26][27]. Generally, the individual characteristics have to improve to meet the demands of the participants to improve the effectiveness of the TPs.…”
Section: Resultssupporting
confidence: 86%
“…Studies show that S-BPD programmes enhance teachers' professionalism. For instance, Wambugu et al (2019) investigated the S-BPD programmes in Kenya and noted that they helped teachers to gain professional growth through collaborative learning with colleagues. Similarly, in Zambia, Haßler et al (2014) revealed that S-BPD improved teachers' thinking capacity and their ability to interact in lessons and improvise teaching materials.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The reviewed literature concisely indicates that the areas and aspects considered in TPD initiatives, particularly S-BPD programmes differ according to time and context. However, previous studies on S-BPD largely focused on pedagogical and managerial issues, experiences, attitudes, challenges and opportunities in general (Asterhan and Lefstein, 2024;Avidov-Ungar, 2020;Hardman et al, 2015;Ke et al, 2019;Kitta, 2015;Mwakabenga et al, 2022;Rugambwa et al, 2022;Wambugu et al, 2019) and paid little attention to the opportunities for promoting teacher ethics through S-BPD programmes. As a result, there is a paucity of literature on the opportunities for promoting teacher ethics through S-BPD.…”
Section: A Synthesis Of Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The terms staff development, in-service training, professional learning, and ongoing education are frequently used. Teacher professional development encompasses ongoing education for educators, including all forms of learning after completing their first training, as defined by [2]. According to [3], the term "professional development" refers to procedures, actions, and activities for teachers to enhance their knowledge, teaching abilities, and teaching attitudes to improve students' learning.…”
Section: Introductionmentioning
confidence: 99%